Integration of Green Products and Green Packaging at Moksa Restaurant in Ubud Bali - I Nyoman Widiana; I Ketut Wardana; I Gusti Ngurah Pertu Agung (Jurnal Ilmiah Hospitality Management, 2026)
Today, global environmental awareness is driving eco-friendly innovation in the restaurant industry. This research aims to explore the innovation practices of green products and green packaging at Moksa Restaurant, Ubud, Bali. Using a descriptive qualitative approach, data was collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that Moksa Restaurant develops plant-based and organic menus sourced from its own permaculture gardens and local farmers, while utilizing eco-friendly packaging such as banana leaves, recycled cardboard, and cassava-based bags. This study concludes that the synergy between the global Triple Bottom Line (TBL) frameworks and the local wisdom of Tri Hita Karana (THK) positions Moksa Restaurant as a contextual integration of the global sustainability framework with local cultural values in culinary business practices. It recommends the further development of green business policies and strategies, and also contributes managerially to the implementation of green products and packaging to support sustainable tourism.